ANALISIS KESALAHAN SISWA KELAS IX SMP NEGERI 14 PALU DALAM MENYELESAIKAN SOAL BILANGAN BERPANGKAT - Wardhani, Ardyah Zahra; Hadjar, Ibnu; Karniman, Tegoeh S.; M., Bakri (Aksioma, 2025)
Based on the results of observations conducted by researchers on students of class IX SMP Negeri 14 Palu, namely working on practice questions related to exponents and there were several problems found, namely 1). Not all students understand the material on exponents 2). there are errors in solving the questions, namely in the exponent section. 3). some students can solve the questions until the middle, and 4). no students are able to finish. This study aims to analyze the errors of class IX students of SMP Negeri 14 Palu in solving exponent number problems. This type of research is descriptive research. The approach used in this study is a qualitative approach. The sample in this study was class IX Kihajar students of SMP Negeri 14 Palu consisting of 37 students, then given a test consisting of 5 questions on exponent number material and then 1 male and female student were selected who made the most mistakes. The results of this study indicate that the errors made by male students in solving exponent number problems are: (1) conceptual errors, namely students' errors in interpreting exponents. (2) principle error, students do not follow the steps that should be written in solving the problem. (3) Arithmetic operation error, students write the wrong answer from the multiplication result. (4) Fact error, namely students make mistakes in using operation symbols. The results of this study indicate that the mistakes made by female students in solving exponent number problems are: (1) Concept error, namely students' mistakes in interpreting the concept of exponents. (2) principle error, students do not write complete steps when solving the problem. (3) Arithmetic operation error, students make mistakes when subtracting, so that it has an impact on the final result. (4) Fact error, namely students make mistakes in using number operation symbols.